Osteopontin Augments M2 Microglia Response and Separates M1- and M2-Polarized Microglial Activation in Permanent Focal Cerebral Ischemia - Anne Ladwig; Helene Luise Walter; Jörg Hucklenbroich; Antje Willuweit; Karl-Josef Langen; Gereon Rudolph Fink; Maria Adele Rueger; Michael Schroeter (Mediators of Inflammation)
Background. Focal cerebral ischemia induces distinct neuroinflammatory processes. We recently reported the extracellular phosphor-glyco-protein osteopontin (OPN) to directly affect primary microglia in vitro, promoting survival while shifting their inflammatory profile towards a more neutral phenotype. We here assessed the effects of OPN on microglia after stroke in vivo, with focus on infarct demarcation. Methods. Animals underwent focal photothrombotic stroke and were injected intracerebroventricularly with 500 μg OPN or vehicle. Immunohistochemistry assessed neuronal damage and infarct volume, neovascularisation, glial scar formation, microglial activation, and M1 and M2 polarisation. Results. After photothrombotic stroke, areas covered by M1 and M2 microglia substantially overlapped. OPN treatment reduced that overlap, with microglia appearing more spread out and additionally covering the infarct core. OPN additionally modulated the quantity of microglia subpopulations, reducing iNOS+ M1 cells while increasing M2 microglia, shifting the M1/M2 balance towards an M2 phenotype. Moreover, OPN polarized astrocytes towards the infarct. Conclusion. Microglial activation and M1 and M2 polarization have distinct but overlapping spatial patterns in permanent focal ischemia. Data suggest that OPN is involved in separating M1 and M2 subpopulations, as well as in shifting microglia polarization towards the M2 phenotype modulating beneficially inflammatory responses after focal infarction.